THE MODERN VIEW AT POSTHUMOUS ORGAN DONATION. FSBI “ACADEMICIAN V.I. SHUMAKOV FRCTAO”, MINISTRY OF HEALTH OF THE RUSSIAN FEDERATION, EXPERIENCE - S. S. Meshcherin; L. V. Belskikh; D. N. Kruglov; A. M. Semyonova (Креативная хирургия и онкология)
The analysis of organizational-methodical, legal and medical aspects of questions on organ donation was conducted on the example of FSBI “Academician V.I. Shumakov FRCTAO”, Ministry of Health of the Russian Federation activity. The question of life threatening emergencies organs transplantation becomes vital in accordance to the widespread growth of patients in the terminal stage of organ dysfunction. The first stage of clinical transplantation is organ donation that is considered to be a complex process, characterized by a large number of involved specialists from different fields of medicine and high level of coordination between them. The human organs donation for transplantation is strictly regulated by Law and it is a form of medical practice, too. The organs removal surgery of a deceased person for transplantation is gradually shifting from unique to regular surgical practice. The gold standard is a multi-organ removal from the donor with the brain death diagnosed, that allows getting the most suitable organs for the transplantation from the same donor. However, it is necessary to continue research in this area to improve the surgical technique of these operations and to make appropriate organizational and methodical efforts to improve the efficiency of the posthumous organ donation program.